Immune checkpoint inhibitor-induced aplastic anaemia: Case series and large-scale pharmacovigilance analysis - Guo, Qian; Zhao, Jin Ning; Liu, Ting; Gao, Jian; Guo, Hui; Cheng, Jing Min (Frontiers in Pharmacology, 2023)
Introduction: Impressive advances in immunotherapy especially immune checkpoint inhibitors (ICIs) have made great progress in treating multiple cancers but can also cause serious even incurable immune-related adverse events (irAEs), mostly found in colitis, dermatitis, hepatitis, and thyroiditis patients. Rare autoimmune hematologic toxicities have been reported in the literature, but are poorly described. Aplastic anaemia (AA) induced by ICIs is a life-threatening autoimmune disease；however, only a few cases have been reported in the literature. Objective: To characterize and evaluate AA associated with different ICI regimens in public database and review the literature. Methods: We described a case series of patients experiencing AA while on ICIs. We also mined the Food and Drug Administration's Adverse Event Reporting System (FAERS) and used reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN) and the multi-item gamma Poisson shrinker (MGPS) algorithms to achieve the data of the suspected adverse events of AA-induced by ICIs between January 2011 and June 2022. Results: Thirteen patients with AA events while on ICIs were included in our case series, and seven of them had a fatal outcome. In FAERS, a total of 38 individual case safety reports (ICSRs) with different ICI regimens were retrieved, of which 25 (65.79%) were reported as monotherapy and 13 (34.2%) had a fatal outcome. The ROR was significant for nivolumab (ROR 3.05, 95%CI 1.73-5.38), pembrolizumab (ROR 2.33, 95%CI 1.16-4.67), avelumab (ROR 12.63, 95%CI 3.15-50.62) and ipilimumab/nivolumab (ROR 2.57, 95%CI 1.15-5.72). Conclusions: There is a significant reporting signal of AA with several ICI agents. Clinicians should raise awareness and monitor this potentially fatal adverse event.